Penataan dan Pembinaan UMKM di Desa Firdaus untuk Peningkatan Ekonomi Kabupaten Serdang Bedagai - Budiman Bonar Alexander Panjaitan; Badaruddin Badaruddin; Zulkifli Zulkifli (Universitas Medan Area, 2025)
This study aims to evaluate the effectiveness of the program for structuring and fostering Micro, Small, and Medium Enterprises (MSMEs) in Firdaus Village, Serdang Bedagai Regency, as well as to analyze the response and strategies of MSME actors in dealing with the program. Using a descriptive qualitative approach, data was obtained through in-depth interviews, observations, and documentation. The results of the study show that although local governments have implemented various training programs, legality assistance, and capital facilitation, the effectiveness of implementation is still limited due to structural obstacles such as budget limitations, lack of participation of business actors, and weak synergy between stakeholders. The response of MSME actors varies widely, ranging from enthusiastic to skeptical, depending on their background and experience. The strategies developed by business actors include adaptation to policies, community collaboration, product innovation, operational efficiency, and strengthening social relations with the government. These findings emphasize the importance of a more participatory coaching approach, based on local needs, and supported by consistent policies and a sustainable mentoring system to encourage inclusive and competitive growth of MSMEs.